Hospital supply of a polymeric enteral nutrition formula amongst inpatients at Patan Hospital, Nepal - Sharma, Bishnu Prasad; Kim, Vicki Leanne (Journal of Patan Academy of Health Sciences, 2022)
Introduction: A retrospective quantitative descriptive study was undertaken to describe the provision of a standard polymeric nutritional supplement produced at Patan Hospital, Nepal, with the aim of assisting efforts to improve the nutritional care of malnourished patients. Method: All adult inpatients (18 years and above) who commenced this nutritional supplement between December 2017 and August 2019 were included. Data was collected from a register and descriptive analysis done. The use across specialty areas, patient weights, duration of use, main feeding route, main volume recommended and main reasons for cessation were among the characteristics described. Result: Total 894 record of the patients were analysed. Awareness-raising activities and launch of a modified supplement recipe, saw prescriptions increase from 13.3 to 47.4 patients per month. The general medical ward and medical intensive care unit initiated the greatest numbers of prescriptions (n=312, n=251 respectively). The nutritional supplement was most commonly prescribed as a 500 ml oral supplement. The average length of prescription was 9.8 d and the main reasons for ceasing was discharge (n=479) and patient expiry (n=158). Weight was recorded in 38% of patients (n=340) and mean weight was 50.5 kg. The average age of the study population was 57.8 y. Conclusion: For improving the nutritional care of malnourished patients, awareness raising activities appeared helpful in increasing prescriptions for the nutritional supplement. However, the use of the nutritional supplement remained low and practices varied significantly between wards.